UNIVOL: protótipo de uma aplicação móvel para divulgação e concentração de vagas de trabalho voluntário no Campus da UFPA - Castanhal - LARDOSA, Afonso Felipe de Jesus (2023)
The economic and social scenario in Brazil imposes the constant search for increasingly qualified professionals. In this sense, higher education stands out as largely responsible for the insertion of professionals in a reality whose job market is gradually demanding. However, university students and initial or even final periods of graduation often report great difficulty in searching for internship opportunities, either due to the requirement of technical knowledge or lack of professional skills. One way to overcome these difficulties is to carry out internships voluntarily, in teaching, research or extension projects, which act as the main solution for improving knowledge and skills. However, the disclosure of vacancies is not always accessible to the entire student community. With that in mind, this work presents a prototype of a mobile application, called UNIVOL, whose objective is to build a platform that concentrates data on vacancies for volunteer internships and expands their access to the academic community on campus I of UFPA Castanhal.